Defining polytrauma by abbreviated injury scale ≥ 3 for a least two body regions is insufficient in terms of short-term outcome: A cross-sectional study at a level I trauma center - Ching-Hua Hsieh; Yi-Chun Chen; Shiun-Yuan Hsu; Hsiao-Yun Hsieh; Peng-Chen Chien (Biomedical Journal, 2018)
Background: Patients with polytrauma are expected to have a higher risk of mortality than the summation of expected mortality for their individual injuries. This study was designed to investigate the outcome of polytrauma patients, diagnosed by abbreviated injury scale (AIS) ≥ 3 for at least two body regions, at a level I trauma center. Methods: Detailed data of 694 polytrauma patients and 2104 non-polytrauma patients with an overall Injury Severity Score (ISS) ≥ 16 and hospitalized between January 1, 2009, and December 31, 2014 for treatment of all traumatic injuries, were retrieved from the Trauma Registry System. Two-sided Fisher exact or Pearson chi-square tests were used to compare categorical data. The unpaired Student t-test was used to analyze normally distributed continuous data, and the Mann–Whitney U-test was used to compare non-normally distributed data. Propensity-score matching in a 1:1 ratio was performed using NCSS software with logistic regression to evaluate the effect of polytrauma on in-hospital mortality. Results: There was no significant difference in short-term mortality between polytrauma and non-polytrauma patients, regardless of whether the comparison was made among the total patients (11.4% vs. 11.0%, respectively; p = 0.795) or among the selected propensity score-matched groups of patients following controlled covariates including sex, age, systolic blood pressure, co-morbidities, Glasgow Coma Scale scores, injury region based on AIS. Conclusions: Polytrauma defined by AIS ≥3 for at least two body regions failed to recognize a significant difference in short-term mortality among trauma patients. Keywords: Polytrauma, Abbreviated injury scale, Injury severity, Monotrauma, Multiple trauma, Mortality